The kinematic features of hyoid bone movement during swallowing in different disease populations: A narrative review - Kuo-Chang Wei; Ming-Yen Hsiao; Tyng-Guey Wang (Journal of the Formosan Medical Association, 2022)
The anterior–superior movement of the hyoid bone plays a significant role in securing the airway and smooth passage of food through the cricopharyngeal muscle. The hyoid bone can be detected easily with instruments such as the videofluoroscopic swallow study (VFSS) and ultrasonography (US), which have made quantitative kinematic analysis possible. Dysphagia is a critical issue in different diseases, including stroke, Parkinson’s disease (PD), head and neck cancer, and amyotrophic lateral sclerosis (ALS), and the data obtained on these diseases from swallowing kinematic analysis has been accumulating. In this review article, we aimed to present the distinct features of kinematic analysis of hyoid movement in stroke, PD, head and neck cancer, and ALS. We also present the possible relationship between altered hyoid kinematics and dysphagia.